Should Individuals Choose Their Own Incentives? Evidence from a Mindfulness Meditation Intervention - Andrej Woerner; Giorgia Romagnoli; Birgit M. Probst; Nina Bartmann; Jonathan N. Cloughesy; Jan Willem Lindemans (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper theoretically and empirically investigates the effects of letting people choose from a menu of increasingly challenging incentive schemes. We derive the conditions under which a policy maker profits from leaving the choice to the individuals by leveraging their private information about the expected benefits from the targeted behavior. We test the theoretical predictions in a field experiment in which we pay participants monetary rewards for completing daily meditation sessions. We randomly assign some participants to one of two incentive schemes and allow others to choose between the two schemes. As predicted, participants sort into schemes in (partial) agreement with the objectives of the policy maker. In contrast to our theoretical predictions, participants who could choose complete significantly fewer meditation sessions than participants that were randomly assigned. Since the results are not driven by poor selection, we infer that letting people choose between incentive schemes may bring in psychological effects that discourage adherence.
Keywords: C90; D03; D80; I10; 330; monetary incentives; dynamic incentives; field experiment; mental health